THE APPLICATION OF MATHEMATICS AT PROBLEM SOLUTIONS IN TECHNICAL SUBJECTS - LABAŠOVÁ, Eva; TRUBENOVÁ, Jaroslava; LABAŠ, Vladimír (Trends in education, 2010)
The relationship between mathematics and solving selected problems in physics and mechanics of rigid and solid bodies is presented in this paper. Aim is to show the mutual connectivity among subjects, very often omitted in teaching of individual subjects. The typical problems of the special technical subjects - mechanics and physics, which require the application of the knowledge of higher mathematics (derivation of the functions of one real variable) are presented.
Keywords: derivation of the function; kinematics of point; bending moment; transverse force.